Structural Change and Per Capita Income in Nepal: Empirical Evidences - Bhatta, Guna Raj (NRB Economic Review, 2014)
This paper empirically examines Nepalese economic structure by applying OLS technique on the annual series of sectoral growth, population and capital related variables ranging from 1975 – 2012. The estimates obtained with due consideration of stationarity of the series including HP filter revealed that industrial sector is significant to increase per capita income compared to the agriculture and service sectors in Nepal. Moreover, health as indicated by life expectancy and population at working age are found to be substantial to increase the income but, education and capital formation are found insignificant. It is inferred that employment matters for raising per capita income, requiring employment-led growth rather mere growth of economic sub-sectors. Hence, it is needed to have balanced contribution of economic sub-sectors and their employment share to national economy along with healthy workforce to raise the per capita income.